ANALYSIS OF FEASIBILITY OF TOFU HOME INDUSTRY IN EAST LOMBOK DISTRICT - Ziheti Sukma Lestari (Journal of Agri Rinjani: Social Agricultural Economics - Faculty of Agriculture, UGR, 2021)
Home industry is a production system that generates added value which is carried out at the home industry and a factory. Generally, home industries are classified as informal sectors that produce uniquely, related to local wisdom, local resources and prioritize handmade. The home industry operate on a small scale, from a non-professional workforce and start from a small capital. The ingredients of tofu for home industry is soybeans that are crushed into soy porridge. Tofu is also quite popular because it is cheap and nutritious. The purpose of this study was to determine the income of the tofu home industry and to find the feasibility of home industry of tofu in East Lombok Regency. This study used descriptive methods, data collection techniques using questionnaires/questionnaires and direct interview techniques. Meanwhile, the location of the research was determined by purposive sampling in two sub-districts, such as Aikmel and Masbagik sub-districts with the consideration that the two sub-districts are the most tofu industrial areas. The number of respondents as many as 30 people who had been determined by Quota Sampling. Determination of respondents in the sample sub-districts was determined by proportional random sampling. The income earned by tofu entrepreneurs was Rp. 264,864/day and the R/C ratio was Rp. 125. So the tofu home industry in East Lombok Regency was feasible to be cultivated. Keywords: homeindustry, income, tofu,